The Influences of Perceived Food Quality, Price Fainess, and Satisfaction on Customers Revisit Intentions Towards Consume Organic Food Restaurants in Yogyakarta - Rakha Fathin Prakoso; Raden Roro Ratna Roostika (Syntax Literate, 2023)
When COVID-19 began to attack various countries, people began to realize how important it is to eat healthy food. People started looking for healthy food even when they ate at restaurants. This study aims to conduct research on people's interest in buying organic food in restaurants in Yogyakarta using two theories: Theory of Planned Behavior and Theory of Consumer Behavior. The aim is to find out whether there is a positive relationship between Perceived Food Quality to Price Fairness, and Customer Satisfaction, Price Fairness to Customer Satisfaction, and Satisfaction to Revisit Intention, to restaurants in Yogyakarta. A total of 250 people participated in the study by filling out questionnaires, and data processing programs using SMART PLS. The results showed that there was a positive relationship between the following variables: perception of food quality with price fairness, perception of food quality with customer satisfaction, price fairness with customer satisfaction, and customer satisfaction with the intention of visiting again.